A numerical study of transient natural convection of water near its density extremum - Othman, Safiah (2005)
This numerical (CFD) study investigates the transient natural convection of water near its density extremum in enclosed spaces. Two cases are considered: flows in rectangular cavities; flows within a vertical cylindrical geometry. A non-Boussinesq approach is employed for both cases and the results are compared to previous studies. For the first case of rectangular cell, the cavity was not filled completely full of water, and a small gap is left at the top in order to have a free surface. Simulations are carried out with water having initial temperatures of 8, 12, 16 and 20 °C, which is equal to temperature of the opposing walls, while the entire cavity is insulated. The fluid is initially still and the temperature of one vertical wall is suddenly lowered to 0 °C. Measurements of the temperature distributions in the cavity were made at three different vertical positions: yl = 0.01785 m,y2 = 0.07545 m andy3 = 0.1353 m. Comparison of both predicted flow patterns and calculated temperatures to the previous study are presented, which confirms that good agreements are obtained. For the second case of vertical cylinder, distilled water having initial temperature of 8 °C is used as the medium, while the entire cavity is insulated. This experimental chamber is enclosed within another glass cylinder, and coolant fluid at a fixed temperature of 0 °C is pumped continuously through the annular region between the cylinders. The comparisons of cooling curves with previous work are made at three different vertical heights of 32, 64 and 96 mm. Results of cooling curve measurements and the flow patterns present good agreement. From the resulting numerical output of both cases, it is evident that the density inversion of water has a significant influence on the natural convection in the cavity.